The deaf cannot see: An accumulation of blindness and deafness as combined theme in Isaiah 42 and 43 - Chris van der Walt (In die Skriflig, 2014)
In the Bible the words blindand deafoccur nine times in the same sentence. An accumulation of such sentences is found in Isaiah 42 and 43, where it occurs three times (Is 42:18, 19; 43:8). Blindness is also mentioned in two further sentences in these chapters. Not only is it stated that the people of God is blind, but Israel also accuses Yahweh that their way is hidden from him (Is 40:27). It is because of this accusation, pertaining to an alleged blindness on Yahweh’s side, that the question of hearing is raised. He answers to this accusation in the heavenly court with the questions ‘Do you not know? Have you not heard?’ From there on God makes it clear that seeing is dependent on hearing. In a heavenly court of law, the wrong perception that God’s people had about the exile was put straight and a new beginning for the exiles was subsequently made. The theme of blind- and deafness is thereby continued from Isaiah 1 and 6 in the verdict in the heavenly court in Isaiah 43, where it became clear that the cure for the spiritual blindness of God’s people is not related to their eyes, but to their ears.